Sequencing the Genome of Indian Flying Fox, Natural Reservoir of Nipah Virus, Using Hybrid Assembly and Conservative Secondary Scaffolding - Fouret, Julien; Brunet, Frédéric G.; Binet, Martin; Aurine, Noémie; Enchéry, Francois; Croze, Séverine; Guinier, Marie; Goumaidi, Abdelghafar; Preininger, Doris; Volff, Jean-Nicolas; Bailly-Bechet, Marc; Lachuer, Joël; et al. (Frontiers in Microbiology, 2020)
Indian fruit bat, flying fox Pteropus medius was identified as an asymptomatic natural host of recently emerged Nipah virus, which is known to induce a severe infectious disease in humans. The absence of P. medius genome sequence presents an important obstacle for further studies of virus-host interactions and better understanding of mechanisms of zoonotic viral emergence. Generation of the high-quality genome sequence is often linked to a considerable effort associated to elevated costs. Although secondary scaffolding methods have reduced sequencing expenses, they imply the development of new tools for the integration of different data sources, to achieve more reliable sequencing results. We initially sequenced the P. medius genome using the combination of Illumina paired-end and Nanopore sequencing, with a depth of 57.4x and 6.1x, respectively. Then, we introduced the novel scaff2link software to integrate multiple sources of information for secondary scaffolding, allowing to remove the association with discordant information among two sources. Different quality metrics were next produced to validate the benefits from secondary scaffolding. The P. medius genome, assembled by this method, has a length of 1,985Mb and consists of 33,613 contigs and 16,113 scaffolds with a NG50 of 19Mb. At least 22.5% of the assembled sequences is covered by interspersed repeats already described in other species and 19,823 coding genes are annotated. Phylogenetic analysis demonstrated the clustering of P. medius genome with two other Pteropus bat species, P. alecto and P. vampyrus, for which genome sequences are currently available. SARS-CoV entry receptor ACE2 sequence of P. medius was 82,7% identical with ACE2 of Rhinolophus sinicus bat, thought to be natural host of SARS-CoV. Altogether, our results confirm that a lower depth of sequencing is enough to obtain a valuable genome sequence, using secondary scaffolding approaches and demonstrate the benefits of the scaff2link application. The genome sequence is available now to the scientific community to proceed with further genomic analysis of P. medius and to characterize the strategies used by of Nipah virus for maintenance and perpetuation in its bat host, monitoring their evolutionary pathways towards a better understanding of bats’ ability to control viral infections.